2015
DOI: 10.1002/pbc.25792
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Cancer Immunotherapy with WT1 Peptide Vaccination for Solid and Hematological Malignancies in Children

Abstract: WT1 vaccination is a safe immunotherapy and induced WT1-specific CTL responses in children; however, as a single agent, vaccination only provided patients in remission, but with a high risk of relapse, with "long-term benefits" in the context of its use for relapse prevention. WT1 peptide-based treatments in combination with other modalities, such as anti-tumor drugs or immunomodulating agents, need to be planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…Since allo-HSCT is a kind of immunotherapy targeting alloantigens, the WT1 peptide vaccination after allo-HSCT constitutes a combination treatment comprising 2 different immunotherapies. Consistent with this result, Sawada et al [26] also reported that a pediatric patient with ALL, who was in CR but at high risk of relapse after allo-HSCT and was treated with the vaccine, showed long-lasting CR. In 2013, Maeda et al [27] reported promising results for the WT1 peptide vaccination after allo-HSCT for the prevention of relapse of AML and ALL, in which HLA-A*2402-positive adult patients were treated by i.d.…”
Section: Clinical Studies Of Wt1 Peptide Vaccine In the 'Advanced Phasupporting
confidence: 67%
See 2 more Smart Citations
“…Since allo-HSCT is a kind of immunotherapy targeting alloantigens, the WT1 peptide vaccination after allo-HSCT constitutes a combination treatment comprising 2 different immunotherapies. Consistent with this result, Sawada et al [26] also reported that a pediatric patient with ALL, who was in CR but at high risk of relapse after allo-HSCT and was treated with the vaccine, showed long-lasting CR. In 2013, Maeda et al [27] reported promising results for the WT1 peptide vaccination after allo-HSCT for the prevention of relapse of AML and ALL, in which HLA-A*2402-positive adult patients were treated by i.d.…”
Section: Clinical Studies Of Wt1 Peptide Vaccine In the 'Advanced Phasupporting
confidence: 67%
“…As is described later in more detail, patients with acute lymphoblastic leukemia (ALL) in CR but with a high risk of relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT) showed long-term maintenance of CR when treated with the WT1 peptide vaccine, which strongly suggests that ALL also constitutes a target disease for this vaccine therapy [25][26][27].…”
Section: Potential Target Hematological Malignancies Other Than Aml Amentioning
confidence: 97%
See 1 more Smart Citation
“…[16][17][18][19] In this pilot study, despite the small number of patients, we describe one of the first attempts to apply DC-based cancer vaccines to the allogeneic setting. We demonstrate that not only is this approach safe and feasible, but that vaccination can be used to sensitize the allogeneic donor Although the allogeneic effect contributes to the success of HCT in ALL, a number of factors are believed to limit the GVL effect in ALL, making the immune response seen in this trial even more notable.…”
Section: Discussionmentioning
confidence: 98%
“…Experience with DC vaccination, particularly in the allogeneic post-transplant setting, is limited. [16][17][18][19] We describe results from a pilot trial that incorporates antigen-specific immunotherapy and allogeneic adoptive cell transfer for pediatric and adult patients with relapsed hematologic malignancies after allogeneic HCT using GMP methods for ex vivo generation of monocytederived dendritic cells. 20 The primary objectives were to assess safety and feasibility of a WT1 peptide-loaded, HLA-A2 restricted, allogeneic donor-derived dendritic cell (DC) vaccine designed to enhance the GVL effect of co-administered DLI.…”
Section: Introductionmentioning
confidence: 99%